1988
DOI: 10.1111/j.1423-0410.1988.tb03904.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Heat Treatment of Factor VIII Concentrate

Abstract: Two batches of heat-treated factor VIII concentrate were found to contain anti-HIV-positive plasma donations. The batches were dry-heat-treated at 68 degrees C for 2 and 24 h, respectively. No HIV seroconversions occurred in 13 susceptible haemophiliacs receiving a total of 540 bottles of these factor VIII preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…[21][22][23][24] Studies of currently licensed products have demonstrated a high degree of safety; there have been no HIV infections with any product currently licensed in the United States. 5,[25][26][27][28][29][30][31][32][33] However, it should be emphasized that the rarity of these infections requires that many patients be enrolled in these trials. An incidence of 1 infection per 1000 patients per year would not be detectable in a trial of 40 or 50 patients.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…[21][22][23][24] Studies of currently licensed products have demonstrated a high degree of safety; there have been no HIV infections with any product currently licensed in the United States. 5,[25][26][27][28][29][30][31][32][33] However, it should be emphasized that the rarity of these infections requires that many patients be enrolled in these trials. An incidence of 1 infection per 1000 patients per year would not be detectable in a trial of 40 or 50 patients.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%